Corporate investment, cash flow level and market imperfections: The case of Norway - B. Gabriela Mundaca; Kjell Bjørn Nordal (University of Oslo, Department of Economics, 2007)
We analyze firms' investment behavior, differentiating firms according to the cash flow levels they experience during their lifecycles. We consequently consider the firm as the basic unit and not firm-year observations. Firms with persistent positive cash flow show higher investment-cash flow sensitivity than firms with persistent negative cash flow. Independent of the industry they belong to, older firms with positive cash flow show a weaker sensitivity than younger firms with positive cash flow. Firms with persistent negative cash flow are neither younger nor smaller than their counterparts, and their cash flow coefficient can be positive, negative or statistically insignificant. Thus, classifying firms by age or size may not yield a group of firms with similar financial structures.
Keywords: D21; G31; G32; 330; Financial constraints; internal funds; investment-cash flow sensitivity; Unternehmensfinanzierung; Betriebswirtschaftliche Investitionstheorie; Kapitalflussrechnung; Norwegen